the PENGARUH MEDIA WAYANG KERTAS TERHADAP KETERAMPILAN MENCERITAKAN KEMBALI ISI CERITA FABEL SISWA KELAS VII SMP NEGERI 3 TEBING TINGGI TAHUN AJAR 2023/2024 - Nysa Maydina Siahaan (Indonesian language and literature education program Majapahit Islamic University, 2023)
The aim of this research is to determine the effect of paper puppet media on the skills of retelling the contents of fable stories of class VII students at SMP Negeri 3 Tebing Tinggi for the 2023/2024 academic year. The design of this research is a one group pretest-posttest experimental research design. The research subjects were students in class VII-3 of SMP Negeri 3 Tebing Tinggi for the 2023/2024 academic year. The data collection method uses an oral test. The data for this research are test scores on the skill of retelling the contents of a fable story without and using paper puppets. The results of this research are that the average score for the skill of retelling the content of a fable story using paper puppet media is in the good category, namely 72.96, while the average score for the skill of retelling the content of a fable story before using paper puppet media is in the fair category, namely 59.25. Based on the results of hypothesis test calculations, the tcount is 2.58. Next, it is compared with ttable with a significance level of ? = 0.05 with dk n-1= 27-1=26, obtained ttable which is 1.706. So it can be concluded that tcount > ttable, namely 2.58>1.706. This means that Ho is rejected, if Ho is rejected then Ha is accepted. This shows that there is a significant influence of the use of paper puppet media on the skills of retelling the content of fable stories of class VII students at SMP Negeri 3 Tebing Tinggi for the 2023/2024 academic. Keywords: paper puppet media, retelling skills, fables